Analisis Penggunaan Media Video pada Mata Pelajaran IPA di Sekolah Dasar - Sonia Mahari Risky (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2019)
Abstract: This study aims to photograph the phenomena that exist by analyzing the use of video media, especially in learning science in SD Muhammadiyah 1 Tulungagung. This research uses qualitative descriptive research type. The research subjects were class teachers and all fifth-grade students of SD Muhammadiyah 1 Tulungagung. The instruments used were observation checklist and Likert scale type questionnaire and interview guidelines. The data analysis technique is a qualitative data analysis technique consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of the study related to the use of video media that have been applied to science subjects in class V SD Muhammadiyah 1 Tulungagung seemed to be able to foster attention and increase students' ease in understanding science subject matter. Moreover, through the use of video media in science lessons, it received a positive response from teachers and fifth-grade students at SD Muhammadiyah 1 Tulungagung even though there were several obstacles faced by the teacher. Abstrak: Penelitian ini bertujuan untuk memotret fenomena yang ada dengan mengalisis penggunaan media video khususnya di dalam pembelajaran IPA di SD Muhammadiyah 1 Tulungagung. Penelitian ini menggunakan jenis penelitian deskiptif kualitatif. Subjek penelitian adalah guru kelas dan seluruh siswa kelas V SD Muhammadiyah 1 Tulungagung. Instrumen dalam penelitian yaitu ceklis observasi, angket jenis skala Likert, dan pedoman wawancara. Teknik analisis data yaitu teknik analisis data kualitatif yang terdiri dari pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian terkait dengan penggunaan media video yang telah diterapkan pada mata pelajaran IPA di kelas V SD Muhammadiyah 1 Tulungagung tampak dapat menumbuhkan perhatian dan menambah kemudahan siswa dalam memahami materi pelajaran IPA. Terlebih lagi melalui penggunaan media video dalam pelajaran IPA mendapat respon positif dari guru dan siswa kelas V di SD Muhammadiyah 1 Tulungagung meskipun ada beberapa kendala yang dihadapi oleh guru.